Procesos de Adquisiciones, Registros Contables y Control Interno de la Sub-Zona de Policía Los Ríos N° 12 - Caiza Hervas, Ruth María (2017)
The present case study is undoubtedly a subject from which we can extract many questions and therefore a problem, the same that seeks to develop and develop solutions that lead to an improvement in the activities concerning this field of study. This time is based on the Procurement Processes, Accounting Registers and Internal Control of the Police Sub-Zone Los Ríos No. 12. Likewise once the subject has been raised, it is necessary to study and analyze the inconsistencies that are presented in the accounting records of the procurement processes due to deficiencies in internal control, which would give rise to the evaluation of the entity and specifically in areas where they handle this and those responsible for those activities are strictly responsible. It is obligatory to work undoubtedly on the aspects and guidelines that concern the Organic Law of the National System of Public Procurement which adheres to the National Public Procurement Service, as well as the requirement of Internal Control Standards for Entities, Public sector, not to mention one of the most essential parts with respect to the management of the monetary species assigned to companies and public bodies and that by means of which the respective accounting records of all those acquisitions of goods or services that are executed and register through the National System of Public Finance and its Financial Management System tool (eSIGEF).